Prediction of bipolar disorder from mental episodes using machine learning approach - Tasmeem, Sumaiya; Rahaman, Motiur; Piasha, Karishma Meherin Khan; Yasar, Samin; Dina, Murshida Akter (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.